Hypnosis. Weight loss without dieting [videorecording (DVD)] - Hepburn, Susan (Susan Elizabeth); Gray, Ken director (Bodhi Lifestyle : BFS Entertainment & Multimedia Limited, 2008)
Professional hypnotherapist Susan Hepburn helps you to achieve your targeted size and weight through easy, safe, and effective hypnosis.